How I Want to Be Seen: Instagram “Staycation” Presentation of Jakarta’s Entry-Level Employees - Haikal Jordy; Virienia Puspita; Esther Suhana Abdurahim; Melati Ratimanjari; Muhammad Aras (Cv. Utility Project Solution, 2023)
Luxury hotels and online travel agents are aggressively promoting new ways to stay at hotels by offering staycation promotions. Staycation has become a new trend starting from the COVID-19 global pandemic and this trend continue until now (the post COVID-19 global pandemic era). This strategy is effective in attracting local tourists, especially young people among entry-level employees who cannot afford to rent the luxury hotel room in normal price. Staycation has become a lifestyle especially in the capital city of Jakarta. This study explores an online self-presentation frame on Instagram in the realm of tourism. Using Erving Goffman's Self Presentation analysis, with a phenomenological approach, this research result shows self-presentation of entry-level employees on Instagram, can be categorized into 7 categories, namely Trendsetter, Popularity Seeker, Poetic, Acting Mysterious, Affectionate, Flexing, and The Bluffer. With the desired image they want to display, which is cool, popular, rich, elegant, sociable, fancy, fun, and full of excitement.